Effect of yogasana intervention on standing balance performance among people with diabetic peripheral neuropathy: A pilot study - Jinny P Kanjirathingal; Rajani P Mullerpatan; Girish Nehete; Nagarathna Raghuram (International Journal of Yoga, 2021)
Background: Diabetic peripheral neuropathy (DPN) is known to cause impaired balance and eventually increased risk of fall. Yogasanas characterized by slow, gentle transitions into postures with a varying base of support and focus on body awareness during movement hold potential for training balance control. Therefore, the current study aimed to evaluate effect of structured Yogasana intervention compared to conventional balance exercise on static and dynamic balance performance among people with diabetic neuropathy. Methods: Thirty-five people with DPN aged 42–70 years were recruited to Yogasana intervention group (n = 11), conventional balance exercises group (n = 10), and Control group (n = 14) following ethical approval. All participants were evaluated at baseline and post 12-week intervention on star excursion balance test, single-limb stance test, and center of pressure (CoP) excursion for balance performance, Modified fall efficacy scale for fear of falls and lower extremity strength using chair stand test and step-up test. Results: Balance performance (static and dynamic measured by star excursion balance test, single-limb stance test, and CoP excursion, lower extremity strength (using chair stand test and step-up test) demonstrated improvement and fear of fall reduced among Yogasana intervention group (p = 0.05) and conventional balance exercises group (p = 0.05) post 12-week intervention. CoP excursion increased in the control group indicating deterioration in balance performance after 12 weeks (p = 0.05). Post hoc comparison revealed that Yogasana intervention was marginally more effective in improving static and dynamic balance performance compared to conventional balance exercises in all variables of standing balance performance (p = 0.025). Conclusion: Yogasana and conventional balance exercises were effective in improving static and dynamic balance performance, lower extremity muscle strength, and reducing fear of fall among people with DPN. Yogasana intervention demonstrated marginally greater improvement in static and dynamic balance performance and lower extremity muscle strength compared to conventional exercise.